Book Review: Kembali Ke Masa Lalu, Solusi Masa Kini - Giovanni, Davin (Sekolah Tinggi Teologi Baptis Indonesia, 2025)
The book “Kembali ke Masa Lalu, Solusi Masa Kini” by Agustinus M.L. Batlajery was born out of concern over two issues: the tendency of contextual theology to disregard the Bible and church tradition, and the threat of radical groups seeking to replace Pancasila as the foundational ideology of the Indonesian state. Batlajery invites readers to learn from the 16th-century church reformation led by Martin Luther and John Calvin, who returned to the sources of Christian faith—namely, the Bible and the writings of the Church Fathers, especially Augustine. The second chapter highlights the importance of a contextual theology that remains rooted in the tradition of faith while being relevant to the realities of society, particularly in Indonesia. In the third chapter, Batlajery offers a solution in the form of the concept of a “Pancasila Renaissance,” a call to return to Pancasila as the foundation of national and societal life. Just as the church reformation was grounded in the past, Batlajery emphasizes that Indonesia’s future must be built by returning to the authentic values of Pancasila.